KESUKSESAN DAN KEGAGALAN IMPLEMENTASI SISTEM ERP: APAKAH KESALAHAN PERANTI LUNAK? - Wahyu Agus Winarno (JURNAL AKUNTANSI UNIVERSITAS JEMBER, 2010)
Enterprise Resource Planning (ERP) are information systems that destined for firm manufacturing and also service that gets role to integrate and automates business process that is engaged operation aspect, production, and distribution at firm. ERP systems is a packaged business software system that enables a company to manage the efficient and effective use of resources and providing a total integrated solution for the organization's information-processing needs. But, ERP systems success own is not easily to be reached, because ERP software is not something that while is assembled/ implementation gets to walk success by itself. In this article tries to identify critical success factors (CSFs) ERP implementation. There are 14 CSFs and 10 failure factors that shall be regarded in the ERP Implementation. Keywords: ERP; ERP Implementation; critical success factors.